2015
DOI: 10.1088/0953-2048/28/10/104006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization ac loss reduction in HTS CORC®cables made of striated coated conductors

Abstract: High temperature superconductors (HTSs), like for instance REBCO (RE=rare earth) coated conductors, are of high potential for building large superconducting magnets. Some magnets, such as accelerator magnets, require the use of superconducting cables to allow fast ramping, and low magnetization loss to mitigate field quality issues. One of the methods to lower ac loss is to divide the superconducting layer in the tape into filaments. In this paper, conductors with copper stabilization for practical applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 22 publications
(37 reference statements)
1
56
0
Order By: Relevance
“…If the assumption holds, small winding angles (longer pitches) are favored for a helical tape configuration as they reduces the axial strain, as shown by (10). This assumption is supported by the experimental results on helically wound tapes in tension [18] and compression [50].…”
Section: Discussionmentioning
confidence: 67%
“…If the assumption holds, small winding angles (longer pitches) are favored for a helical tape configuration as they reduces the axial strain, as shown by (10). This assumption is supported by the experimental results on helically wound tapes in tension [18] and compression [50].…”
Section: Discussionmentioning
confidence: 67%
“…In order to validate the model, AC losses were calculated and compared to those published in [38]. The geometrical and physical properties were chosen in accordance with [38], as shown in Table 1. Two CORC cable samples are wound from REBCO tapes, which are named as Cable B and Cable C. Cable B has two layers and each layer is wound with 3 tapes.…”
Section: Model Validationmentioning
confidence: 99%
“…A laser scribing technology has been applied on REBCO tapes to reduce AC losses, in which the superconducting layer of the tape is divided into filaments by laser scribing and meanwhile the substrate layer is kept for a mechanical support [38,42]. This section focuses on the magnetization loss reduction using striated tapes for CORC cables.…”
Section: Loss Reduction Using Striated Rebco Tapesmentioning
confidence: 99%
See 1 more Smart Citation
“…A great number of research groups as well as manufacturers have been focusing on investigating the magnetization AC loss and transverse resistivity of striated tapes [3][4][5][6][7][8]. Lots of researchers has confirmed that striation is an effective way to reduce the hysteresis AC losses.…”
Section: Introductionmentioning
confidence: 99%